MENINGKATKAN MOTIVASI BELAJAR SISWA DENGAN MENGGUNAKAN MEDIA AUDIOVISUAL DALAM PEMBELAJARAN SENI BUDAYA KELAS VII DI SMP NEGERI 1 PAINAN - Putri Johana; Harisnal Hadi; Yos Sudarman (FBS Universitas Negeri Padang, 2018)
Abstract This article aims to improve students' learning motivation by using audiovisual media in learning the art of music. The type of this research was classroom action research held in 2 cycles. The object of the research was the students of class VII-3, amounting to 32 students with 15 male students and 17 female students. The research instrument was the researcher herself and the teacher of Art Culture as observer. Data collection techniques used were observation, interview, questionnaire, literature study, and motivational observation sheet with happy indicator, attention, concentration, and persistence. The results showed that learning the art of music by using audiovisual media could improve students' learning motivation in class VII-3, and had a good impact on the process of learning music. This statement was evidenced by the average percentage of each indicator of motivation to learn which was on the indicator happy with the average percentage of 59% increased to 78%, and the indicator attention with the average percentage of 44% increased to 76%, the indicator concentration with the average- average percentage 45% increased to 78%, and persistence indicator with average 42% percentage increased to 73%. Thus, from result of observation obtained that the result of student learning motivation in cycle I with average 47% categorized medium and increased in cycle II become 76% categorized very high. Moreover, the results of questionnaires that have researchers distributed to students there was an enhancement that was in cycle I obtained by 76% percentage and in cycle II 88%. In summary, authors can draw the conclusion that the using audiovisual media learning art music in class VII-3 SMP Negeri 1 Painan has succeeded increase student learning motivation. Keywords: Improving Learning, Motivation, Audiovisual Media, Art and Culture